Implementation of interactive three-dimensional visualization of air pollutants using WebGL. (April 2019) - Liu, Dongwei; Peng, Jie; Wang, Yanyu; Huang, Meijin; He, Qianshan; Yan, Yafei; Ma, Bingxin; Yue, Caijun; Xie, Ying
Abstract: The visualization of a three-dimensional (3D) distribution of high-density data for scientific computations with limited computing resources under a network environment is difficult. This paper describes the implementation of an interactive 3D display of air pollutants in a network environment using the open-source WebGL class library, Three. js. A kd-tree is used to find the nearest point data to interpolate the 3D grid data of pollutants because the source data are scattered, which helps locate the data conveniently at the client's end. The binary file format is used to save and transfer data to reduce the number of network transmissions and to improve the speed of the image display. The results show that the visual effects and rendering speed are significantly improved on the web with the use of the proposed technology. Highlights: We developed a method for visualizing three-dimensional pollutant distribution based on WebGL. The visual effects and rendering speed are significantly improved on the web using the proposed technology. The technology can also be used in the 3D display of other scientific data such as meteorological, hydrology data etc.